Immunization of young heifers with staphylococcal immune evasion proteins before natural exposure to Staphylococcus aureus induces a humoral immune response in serum and milk - Lindert Benedictus; Lars Ravesloot; Kim Poppe; Ineke Daemen; Eveline Boerhout; Jos van Strijp; Femke Broere; Victor Rutten; Ad Koets; Susanne Eisenberg (BMC Veterinary Research, 2019)
Abstract Background Staphylococcus aureus, a leading cause of mastitis in dairy cattle, causes severe mastitis and/or chronic persistent infections with detrimental effects on the cows’ wellbeing, lifespan and milk production. Despite years of research there is no effective vaccine against S. aureus mastitis. Boosting of non-protective pre-existing immunity to S. aureus, induced by natural exposure to S. aureus, by vaccination may interfere with vaccine efficacy. The aim was to assess whether experimental immunization of S. aureus naïve animals results in an immune response that differs from immunity following natural exposure to S. aureus. Results First, to define the period during which calves are immunologically naïve for S. aureus, Efb, LukM, and whole-cell S. aureus specific serum antibodies were measured in a cohort of newborn calves by ELISA. Rising S. aureus specific antibodies indicated that from week 12 onward calves mounted an immune response to S. aureus due to natural exposure. Next, an experimental immunization trial was set up using 8-week-old heifer calves (n = 16), half of which were immunized with the immune evasion molecules Efb and LukM. Immunization was repeated after one year and before parturition and humoral and cellular immunity specific for Efb and LukM was determined throughout the study. Post-partum, antibody levels against LukM and EfB were significantly higher in serum, colostrum and milk in the experimentally immunized animals compared to animals naturally exposed to S. aureus. LukM specific IL17a responses were also significantly higher in the immunized cows post-partum. Conclusions Experimental immunization with staphylococcal immune evasion molecules starting before natural exposure resulted in significantly higher antibody levels against Efb and LukM around parturition in serum as well as the site of infection, i.e. in colostrum and milk, compared to natural exposure to S. aureus. This study showed that it is practically feasible to vaccinate S. aureus naïve cattle and that experimental immunization induced a humoral immune response that differed from that after natural exposure only.